Water-use efficiency of soybean (Glycine max) using line-source oprinkler technique - KAUR, PAVNEET; HUNDAL, S S (The Indian Journal of Agricultural Sciences, 2013)
A field study was conducted with a line-source sprinkler technique during rainy season (kharif) 1995 at Ludhianato characterize evapo-transpiration and water-use efficiencyÂ  of soybean [Glycine max (L.) Merr.]. Four water-applicationtreatments (I1' I2, I3 and I4) with progressively decreasing amounts of irrigation were marked in the direction perpendicular to the line source. The I1, I2, I3 and I4 treatments received differential irrigation of 187.8, 136.6,109.1, and 57.9 mm respectively, in addition to season's monsoon rainfall. The cumulative seasonal soil-water use by the crop amounted to 661, 654, 644 and 571 mm for the I1' I2, I3 and I4 treatments respectively. The water-use efficiency of 2.48, 2.46, 2.34 and 2.46 kg/ha/mm for straw yield and 0.826, 0.716, 0.688 and 0.711 kg/ha/mm for seed yield was obtained under the I1, I2, I3 and I4 treatments respectively. A linear relationship between water use and dry-matter production existed for various treatments. Dry-matter production and seed yield were maximum in I1 followed by I2, I3 and I4 treatments (in the decreasing order).